Caregiver experiences, attitudes and perceptions about feeding toddlers and preschool children in Switzerland: a qualitative study. Issue 1 (December 2016) - Jacquier, Emma F.; Gatrell, Anthony; Bingley, Amanda
Abstract Background Young children depend upon caregivers to make healthy food and beverage choices on their behalf. Research to understand caregiver perspectives may help develop interventions to improve diets and offer new insights for healthcare professionals and future nutrition studies. The main study aim was to explore caregiver feeding experiences, with a focus on portion sizes and attitudes towards beverages, for the first time in Switzerland, and contribute to the European perspective in this field. Methods Inductive, qualitative study with purposive sampling of 19 male and female caregivers (low-high income, 20–46y) of children (1–5y) using in-depth interviews. The model, "Food Choice Process over the Life Course", was used as a theoretical framework. Full transcripts underwent a thematic analysis. Key themes were developed from the data. Results Key themes were a) Rules and routines b) Tacit knowledge c) Explicit knowledge d) Managing. Rules about foods and beverages to encourage/limit were widespread. Participants struggled to explain how they portioned foods but offered volume-estimates of beverages portions. Perceptions about health effects of beverages influenced choices. Managing time and budget influenced purchases and meal preparation. There was good agreement with the theoretical framework. Conclusions Rules and routines reflected anti-obesity recommendations and food-choice values. Perceived health effects of certain beverages, cultural classifications of snacking and the influence of income and time highlight multi-level determinants influencing dietary choices about feeding young children. Health-care professionals may wish to consider these emergent themes when advising on early-childhood feeding. Future studies are required to understand more about the attitudes and perceptions of beverages in the diets of toddlers and preschooler, along with perceptions related to snacking behaviours.